1987
DOI: 10.1203/00006450-198702000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dopamine Infusion on Regional Blood Flow in Newborn Lambs

Abstract: ABSTRACT. The purpose of this project was to investigate the effects of high rates of dopamine infusion on cardiac output and regional blood flow in the lamb. We studied eight unanesthetized newborn lambs (mean age 7 + 2 days) during a 15-min baseline period and while infusing dopamine at 5-, 20-, 80-, and 160 pg/kg/min. We measured cardiac output and mean aortic, pulmonary arterial and left atrial pressures, and organ blood flow using radionuclidelabeled microspheres at each rate of dopamine infusion. Cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
(20 reference statements)
2
18
1
Order By: Relevance
“…The cardiovascular effects of dopamine that we observed are consistent, in part, with studies in developing animals suggesting that neonates exhibit relative insensitivity to inotropes, believed to be due to immaturity of cardiac ␤ 1 -adrenergic receptor activity (5,6,8,12,31). In human infants, the cardiovascular effects of dopamine are less consistent, presumably because of the variable physiology of critically ill neonates who require or receive pressors.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The cardiovascular effects of dopamine that we observed are consistent, in part, with studies in developing animals suggesting that neonates exhibit relative insensitivity to inotropes, believed to be due to immaturity of cardiac ␤ 1 -adrenergic receptor activity (5,6,8,12,31). In human infants, the cardiovascular effects of dopamine are less consistent, presumably because of the variable physiology of critically ill neonates who require or receive pressors.…”
Section: Discussionsupporting
confidence: 79%
“…In immature animals, dopamine is a less effective inotropic agent, presumably because of immaturity of cardiac ␤ 1 -adrenergic receptors. Minimal cerebral vasodilatory, or possibly vasoconstrictive, effects might therefore be expected at low or moderate dopamine doses, because development of vascular dopaminergic receptors is also likely to be incomplete, particularly compared with ␣-adrenergic receptors (8,12,30,31).The objective of this study was to describe the cerebrovascular responses of developing fetuses at two gestational ages to increasing doses of intravenous dopamine with and without ␣-adrenergic or dopaminergic (D 1 ) receptor blockade. We tested the hypothesis that dopamine causes dose-dependent cerebral vasoconstriction and that this response may be enhanced because of immaturity of dopaminergic receptor development and increased sensitivity and activation of ␣-adrenergic receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Preload, represented by mean left atrial pressure, did not differ between treatment groups. However, the chloralose-treated group demonstrated increased afterload, indicated by increased systemic vascular resistance, to levels that impair cardiac output both in constantly perfused lamb hearts (16) and in conscious neonatal lambs (17). Therefore, the failure of cardiac output to rise in response to alveolar hypoxia in chloralose-treated lambs must be explained by relationships between hypoxia, increased afterload, and/or reduced contractility.…”
Section: Pulmonary Vascular Resistancementioning
confidence: 98%
“…D levels of 500-750 pg/ml, which are similar to those measured in the present study, have been reported in two recent studies of stressed human newborns (18,19). Results of exogenous D infusions in neonatal lambs suggest that these levels are probably not hemodynamically significant (20). The source of catecholamines in the neonatal circulation is uncertain.…”
Section: Discussionmentioning
confidence: 99%